2022
DOI: 10.3390/molecules27217267
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of In Vivo Existence Forms of Nardosinone in Mice by UHPLC-Q-TOF-MS Technique

Abstract: Nardosinone, a sesquiterpene peroxide, is one of the main active constituents of the ethnomedicine Nardostachyos Radix et Rhizoma, and it has many bioactivities, such as antiarrhythmia and cardioprotection. To elucidate its in vivo existence forms, its metabolism is first studied using mice. All urine and feces are collected during the six days of oral dosing of nardosinone, and blood is collected at one hour after the last dose. Besides, to validate some metabolites, a fast experiment is performed, in which n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Thus, the chemical unstable property is suggested to require adequate consideration in future in vivo investigations on the pharmacokinetic characteristics of nardosinone when orally administered. In light of this, two pharmacokinetic studies of nardosinone were reported using intravenous injection [ 22 ] and oral ingestion [ 23 ] as the routes of administration. However, to date, the metabolites of nardosinone have not been characterized and investigated in depth.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the chemical unstable property is suggested to require adequate consideration in future in vivo investigations on the pharmacokinetic characteristics of nardosinone when orally administered. In light of this, two pharmacokinetic studies of nardosinone were reported using intravenous injection [ 22 ] and oral ingestion [ 23 ] as the routes of administration. However, to date, the metabolites of nardosinone have not been characterized and investigated in depth.…”
Section: Introductionmentioning
confidence: 99%